(untitled) (International Journal of Engineering and Computer Science, 2017)
In this work, PID and modified form of PID (I-PD) controller design procedure is proposed for highly non-linear benchmark electromechanical systems such as Vehicle Active Suspension System (VASS) and Magnetic Suspension System (MSS) discussed in the literature. The proposed controller design is implemented using the most successful heuristic algorithms, such as Particle Swarm Optimization (PSO), Bacterial Foraging Optimization (BFO) and Firefly Algorithm (FA). A weighted sum of objective function comprising the overshoot (Mp), settling time (Ts), integral square error (ISE) and integral absolute error (IAE) is chosen to guide the heuristic search in order to find the controller parameters such as Kp, Ki, and Kd. In the proposed work, the major aim is to compare the performance of the considered heuristic algorithms for the controller design problem. The simulation work is implemented using the Matlab software and the performance of this study is validated using Mp, Ts, ISE and IAE values for the reference tracking and disturbance rejection operations. This study confirms that, FA offers faster convergence compared with the PSO and BFO algorithms.